The digital readiness of school principals in The northern Jordan Valley in the light of Corona pandemic and its impact on administration of administrative tasks from the teachers' point of view - Al-khatib, Yaseen Mohammad (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the digital readiness of school principals in The northern Jordan Valley in the light of the Corona pandemic and its impact on administration administrative tasks from the teachers' point of view, The researcher used the descriptive and analytical method, the tool is a questionnaire that distributed to a group of male and female teachers in public schools and those affiliated to the education directorates in the northern Jordan Valley, which numbered (180) teachers, who were chosen by simple random method, The results of the study showed that the effect of digital readiness of school principals in the light of Corona pandemic in the administration of administrative tasks on an overall average (3.88 out of 5), i.e. an approval degree of readiness (high), There are no statistically significant differences between the arithmetic means of the responses of the sample members to the tool as a whole due to variables (gender, experience, educational qualification), In light of the results, the researcher recommended the necessity of holding workshops and training courses for teachers and school principals to help them use the computer and the Internet efficiently and effectively to deal with the requirements and strategies of digital learning, in addition to supporting the digital readiness of school principals to maintain the permanence and continuity of education in the Jordan Valley and throughout the Kingdom of Jordan and the Arab countries.
Keywords: digital readiness; Corona pandemic; impact; administration of administrative tasks; The northern Jordan Valley; the Hashemite Kingdom of Jordan